Implementing blended learning and gamification to develop learners’ speaking skills in an English-speaking club - Bramy Biantoro; Alimin Adi Waloyo; M. Masduki (Universitas Muhammadiyah Malang, 2024)
This paper aims to elaborate a community service program, which addressed a significant issue in the semi-formal English learning contexts for the secondary level of education. The project aims to improve the quality of English-speaking activities at SMP Muhammadiyah 1 Malang by elevating the quality of the Speaking Club learning media and contents. The main improvement focuses on the integration of blended learning and gamification elements to ensure the sustainability of students’ learning outside the regular classes. The blended learning covers the use of Learning Management System (LMS), specifically Google Classroom, to facilitate continuous and repetitive speaking practices that has excellent quality, such as flexibility, affordability, and accessibility, contributing to increased English-speaking habits among students. Additionally, gamification activities, including Online Scrabble, Guess the Characters, Interactive Flashcards, and Snake and Ladders, are incorporated into Google Classroom to enhance engagement and collaboration. The synergy between blended learning through Google Classroom and gamification activities is expected to elevate English speaking proficiency among students at SMP 1 Muhammadiyah Malang. Furthermore, the project aims to foster a robust partnership between English teachers, University of Muhammadiyah Malang students, and lecturers. The partnership can create a positive impact on the overall educational experience, emphasizing the goal of improving students' communication and speaking abilities beyond the confines of classroom walls.